The strongly dimorphic bark beetle genus Pseudomicracis (Coleoptera, Scolytinae) in Madagascar—an integrated taxonomic revision - Jordal, Bjarte H. (Zootaxa, 2022)
The largely Malagasy bark beetle genus Pseudomicracis Eggers, 1920 is revised based on molecular data and morphological studies. Because the type species P. elsae Eggers, 1920 from Tanzania has no intact type material, the diagnosis is fixed using an auxiliary species, P. madagascariensis (Schedl, 1961), which is typical for the genus and supports the original description of P. elsae. Six new species are described from Madagascar: P. atra Jordal, sp. nov., P. coronata Jordal, sp. nov., P. lauricola Jordal, sp. nov., P. pilosa Jordal, sp. nov., P. verrucosa Jordal, sp. nov., and P. vitrioculata Jordal, sp. nov. Mimiocurus camerunus (Hagedorn, 1909) has no existing type material and is transferred from Pseudomicracis based on Hagedorn’s illustrations of the antenna and protibia. New distributional and host records are given for P. dispar (Schedl, 1961), P. difficilis (Schedl, 1965) and P. madagascariensis (Schedl, 1961). A molecular phylogenetic analysis included 8 of 12 known species, documenting a strongly supported clade of Pseudomicracis species, but with highly uncertain internal relationships. A key and photographs to all Malagasy species are provided.